MAPPING STUDENT’S UNDERSTANDING OF BASIC ACCOUNTING CONCEPT THROUGH ASSESSMENTS DIAGNOSTICS - Herawati, Nyoman Trisna; Made Ary Meitriana; Made Anintia Trisna dewi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Assessment is an important component in the implementation of education, one of which is diagnostic assessment. Diagnostic assessment aims to understand students' initial abilities, so that teachers can design learning methods and media that suit students' abilities. However, the use of diagnostic assessments in mapping the understanding of basic accounting concepts is still very rare. For this reason, this study aims to analyze how diagnostic assessments are given to map students' understanding of concepts. The novelty of this research lies in the use of diagnostic assessments in learning, especially in basic financial accounting materials. The research method used is descriptive which is sourced from the analysis of the results of diagnostic assessment test scores given to 2nd semester students who took the Intermediate Financial Accounting course as many as 48 students. The test scores are then categorized into 3 categories, namely (1) very understanding if the score is >= 85, (2) understanding enough if the score is 70 to 84, and (3) not understanding if the score obtained is < = 69. The mapping of basic accounting concepts in this diagnostic assessment is divided into 7 concept maps, namely (1) Definition of Accounting, (2) Basic Equations of Accounting, (3) Account Concepts, (4) Make the journal entries and posting in ledger, (5) Make the trial balance and adjusting entries, (6) Prepare the financial statement, and (7) Completing accounting cycle by closing entries. The results of the study show that diagnostic assessment can map the understanding of basic accounting concepts in accounting students into 7 concept maps. The average of each concept is as follows: concept 1 is 77, concept 2 is 68, concept 3 is 86, concept 4 is 83, concept 5 is 63, concept 6 is 81, concept 7 is 86. On average, concept 2 is related to the basic accounting equation and concept 5 is the adjustment to obtain the lowest average result compared to other concepts. Furthermore, students' understanding of each concept is analyzed which can then be given a reward for concepts that are still lacking. Based on this, it can be concluded that with a diagnostic assessment of basic accounting concepts, both lecturers and students can find out the weaknesses in each concept. With this mapping, lecturers can design learning strategies that suit the needs of students.